Karakteristik Pembelajaran Dosen Ilmu Al-Qur’an dan Tafsir UIN Raden Mas Said Surakarta Prespektif Permenristekdikti Pasal 11 Nomor 44 Tahun 2015 - Muhammad Habib Zainul Huda; Khoiruddin Nasution (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The quality of educators is something that must always be considered by the government. The quality can be seen from how the characteristics of educators when providing learning in the classroom. This Mini Research will look at the Learning Characteristics of IAT Lecturers at UIN Raden Mas Said Surkarta. In this case, the researcher wants to examine two IAT lecturers only, the two lecturers are: Dr. H. Abdul Matin bin Salman Lc,.M.Ag and Dr. Hj. Ari Hikmawati S.Ag. M.Pd. This research includes descriptive qualitative research analysis. The data collection methods used are questionnaire method and RPS analysis. Respondents of this method are 2 students in each batch. In this case the researchers took from the class of 2016 - 2023, so that the respondents were 16 students. After the data is collected, then the researchers describe, and then the researchers compare and analyze using Permenristekdikti Article 11 Number 44 of 2015 related to “Learning Process Standards”. The conclusion: (1). The learning of IAT lecturers at UIN Raden Mas Said Surakarta is in accordance with the Learning Process Standards in Permenristekdikti Article 11 Number 44 of 2015 which is Integrative-Interconnective. (2). Learning Characteristics of Dr. H. Abdul Matin bin Salman Lc, M.Ag is more about Interactive, Holistic, Scientific, and Contextual learning. (3). Learning Characteristics of Dr. Hj Ari Hikmawati S.Ag. M.Pd is more about Integrative, Thematic, Effective, and Collaborative learning.